Appropriate use criteria for cardiovascular MRI: SIC – SIRM position paper Part 2 (myocarditis, pericardial disease, cardiomyopathies and valvular heart disease). Issue 7 (July 2021) - Francone, Marco; Aquaro, Giovanni Donato; Barison, Andrea; Castelletti, Silvia; de Cobelli, Francesco; de Lazzari, Manuel; Esposito, Antonio; Focardi, Marta; di Renzi, Paolo; Indolfi, Ciro; Lanzillo, Chiara; Lovato, Luigi; et al.
Abstract : N/A: Cardiovascular magnetic resonance (CMR) has emerged as an accurate diagnostic technique for the evaluation of patients with cardiac disease in the majority of clinical settings, thanks to an established additional diagnostic and prognostic value. This document has been developed by a joined group of experts of the Italian Society of Cardiology (SIC) and Italian Society of Radiology (SIRM) to provide a summary about the current state of technology and clinical applications of CMR, to improve the clinical diagnostic pathways and to promote its inclusion in clinical practice. The writing committee consisted of members and experts of both societies in order to develop a more integrated approach in the field of cardiac imaging. This section 2 will cover myocarditis, pericardial disease, cardiomyopathies and valvular heart disease.